Cold War Cosmopolitanism Period Style in 1950s Korean Cinema - Klein, Christina (University of California Press, 2020)
"Han Hyung-mo was a major figure within South Korea's Golden Age cinema. The director of Madame Freedom (1956), the most famous film of the 1950s, Han made popular films that explored women's relationship to modernity. He was also a master stylist who introduced technological innovations and fresh ideas about film form and genre into Korean cinema. This book offers a transnational cultural history of Han's films, one that foregrounds questions of gender and style. Han's films embody a period style that Klein calls "Cold War cosmopolitanism." The waging of the Cold War enmeshed South Korea within a network of ties to the Free World. Fostered by political leaders like Syngman Rhee, American institutions such as the US military and the Asia Foundation, and ordinary Koreans, these networks created channels through which material resources, liberal ideas, and cultural texts flowed into and out of Korea. Han and other cultural producers tapped into these networks to create new forms of commercial culture that meshed local concerns with foreign trends. Combining extensive archival research and in-depth analyses of individual films, Cold War Cosmopolitanism offers a fresh, interdisciplinary perspective on the waging of the cultural Cold War in Asia."